Experiments on the transition of fast to slow bubbles in water. (16th January 2018) - Nüllig, M.; Peters, F.
Highlights: Bubbles have two levels of rise velocity in water. The rotary chamber technique is capable of observing the transition between these levels in terms of velocity and shape. The results show a characteristic behavior supporting the cap formation hypothesis. Abstract: Bubbles have two levels of rise velocity in water called fast and slow. The fast ones are associated with a mobile interface while the slow ones are considered immobile like spheres. Whenever fast bubbles are generated they transfer to slow ones by accumulation of impurities present in the water. In this work we investigate this transfer with a rotary chamber technique. The technique allows the levitation and continuous observation of a bubble on its way from fast to slow. We used standard distilled water conforming to DIN 43530 and VDE 0510 with a specific conductance <10 μS/cm. It led to long transfer periods of up to 45 min. The analysis of the bubble trajectory provided the histories of drag, lift and shape. The overall results support the cap formation theory.